Identity as an Organizing Idea of New Vocabulary and Phraseology - T. V. Leontyeva; A. V. Shchetinina (Научный диалог, 2021)
The vocabulary and phraseology are considered from the standpoint of embodying the idea of identity in them. The relevance of the study is due to the need to assess the dynamics of the vocabulary of the language. It is shown that the idea of identity is verbalized in the nominations of a person according to belonging to a certain social community, which has professional status, generational, class and other characteristics. It is noticed that new phraseological units appear in the language in open groups. The novelty of the research lies in the identification of new phraseological groups, which can be partially or completely subject to lexicography. It is noted that online communication has greatly increased attention to the words group, community and the idea of a publicly represented identity. It is shown that the analytical attitude of modern media has led to an orientation towards reflection and the construction of expert assessments in the form of bright, memorable idioms, the creative class, sofa fighters, etc. The intensification of the processes of the language game is shown by the example of expressions with the word collars, releasing a color code (white, gold, platinum collars, etc.). The Internet is said to have provided opportunities to show multiplying identities. The “fourth wave of words” (after the gangster, professional, glamorous) is proposed to be considered the youth, which is formed in Internet communication and expresses the desire of this age category (youth) to know themselves, their values, belonging, purpose and place in the world.